VOA Special English: Increasing Students’ Speaking Skill at Faculty of Computer Science - Indah Muzdalifah; Lucky Laura Van FC (JEE (Journal of English Education), 2018)
English is a Foreign Language as a subject that has been studying since elementary level. However, there were found minimal skill competence of speaking in Engish. Thus, it needs improvement both from the media system used and the appropriate strategy for the English course as a general basic course in particular in the Faculty of Computer Science. Technology can be an alternative as the media in education prosess. One of these media is Voice of America Special English Education Report. Basicaly, there are several benefits of using this media such as listening; while they are listening VOA automatically they are studying how to pronounce something; another skill is reading and writing skill because this media supported by running text. Thus, automatically this media includes four language skill in English. The subject of this research is Computer science students second semester. The purpose of this research is to find out whether the use of VOA Special English Education report can improve students’ speaking skill in English. The data was collected by applying the speaking test which used rubric scoring. The method of this research is classroom action research. There were two cycles of the test as comparative the improvement of students’ speaking skill in using VOA Special English Education Report . The result of this research that there is significant improvment of using VOA Special English Education Report. The score of the first cycle is 56,8 and the second cyce is 64,8. It means that there is increasing of the score speaking test by using the media VOA Special Engilsh Education Report.